Management News and Notes (Academy of Management Journal, 1966)
The article presents an update on issues related to management as of September 1966. Several books about corporate management have been named winners of the 1965 McKinsey Foundation-Academy of Management Book Awards. The 10th annual meeting of the Midwest Division of the Academy of Management will be held at Northwestern University on April 7 and 8, 1967. Joseph A. Litterer received the eighth annual Organization Development Council Publications Award for his book “Analysis of Organizations.”